Ochrona biorcy kredytu konsumenckiego w regulacjach prawnych Francji - Korenik, Dorota (The Protection of the Consumer Credit's Debtor in French Legislation, 2005)
The article presents the law regulations and the evolution of the consumer credit institution in France according to the EU united market. The premises and economic significance of the institution in the present market economy are indicated.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 167-181